ETIKA KOMUNIKASI ORANG TUA TERHADAP PERKEMBANGAN EMOSIONAL DAN SOSIAL ANAK DI DESA PERTAMPAKAN,KECAMATAN GUNUNG MERIAH KABUPATEN ACEH SINGKIL ( STUDI: KOMUNIKASI PENYIARAN ISLAM) - Clana, Abd Azis; Muhsinah, Muhsinah; Yoga , Salman (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2025)
This study aims to analyze the ethical practices of parental communication and their influence on the emotional and social development of children in Pertampakan Village, Gunung Meriah District, Aceh Singkil Regency. The background of this study is the importance of Islamic communication in shaping children's morals, personality, and social skills, especially amidst the challenges of modernization and digitalization. This study uses a qualitative descriptive-naturalistic method as described by Sugiyono, using purposive sampling involving parents, children, and local community leaders as key informants. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the Miles & Huberman interactive model, which consists of data reduction, data presentation, and conclusion drawing. The research findings reveal that parents in Pertampakan Village generally apply Islamic communication patterns, such as qaulan sadida (honest speech), qaulan layyina (gentle speech), and qaulan ma'rufa (good speech), which positively influence children's emotional stability, self-confidence, and social sensitivity. Furthermore, Islamic communication practices have been shown to strengthen children's politeness, sense of responsibility, and social participation in the family, school, and community. This study concludes that parental communication ethics based on Islamic values ​​play a crucial role in shaping a generation with noble character and a strong sense of social responsibility.